P2X1, P2X4, and P2X7 Receptor Knock Out Mice Expose Differential Outcome of Sepsis Induced by α-Haemolysin Producing Escherichia coli - Greve, Anne-Sofie; Skals, Marianne; Fagerberg, Steen K.; Tonnus, Wulf; Ellermann-Eriksen, Svend; Evans, Richard J.; Linkermann, Andreas; Praetorius, Helle A. (Frontiers in Cellular and Infection Microbiology, 2017)
α-haemolysin (HlyA)-producing Escherichia coli commonly inflict severe urinary tract infections, including pyelonephritis, which comprises substantial risk for sepsis. In vitro, the cytolytic effect of HlyA is mainly mediated by ATP release through the HlyA pore and subsequent P2X1/P2X7 receptor activation. This amplification of the lytic process is not unique to HlyA but is observed by many other pore-forming proteins including complement-induced haemolysis. Since free hemoglobin in the blood is known to be associated with a worse outcome in sepsis one could speculate that inhibition of P2X receptors would ameliorate the course of sepsis. Surprisingly, this study demonstrates that P2X1−/− and P2X4−/− mice are exceedingly sensitive to sepsis with uropathogenic E. coli. These mice have markedly lower survival, higher cytokine levels and activated intravascular coagulation. Quite the reverse is seen in P2X1−/− mice, which had markedly lower cytokine levels and less coagulation activation compared to controls after exposure to uropathogenic E. coli. The high cytokine levels in the P2X7−/− mouse are unexpected, since P2X7 is implicated in caspase-1-dependent IL-1β production. Here, we demonstrate that IL-1β production during sepsis with uropathogenic E. coli is mediated by caspase-8, since caspase-8 and RIPK3 double knock out mice show substantially lower cytokine during sepsis and increased survival after injection of TNFα. These data support that P2X7 and P2X4 receptor activation has a protective effect during severe E. coli infection.